Purification of polluted water with La- and Gd-doped spinel ferrite nanoparticles: adsorption kinetics and mechanisms - Starko, Iryna (Physics and Chemistry of Solid State, 2025)
In this work, the removal of the CR dye and OTC antibiotic from aqueous solutions by as-prepared and annealed La- and Gd-substituted nanoferrites was investigated. The kinetic models of PFO, PSO, Elovich, and IPD were used to evaluate the adsorption mechanism. It was shown, that the adsorption of CR and OTC on the ferrites is the best fitted with the pseudo-second-order kinetic model. The adsorption equilibrium towards the CR and OTC was reached at 60 minutes for both pollutants. The annealing impacts the samples' adsorption properties, increasing the initial rate of adsorption as per the PSO kinetic model. In particular, the initial rate of the CR adsorption on the as-synthesized and annealed La- and Gd-containing ferrites is increased approximately 7 and 5 times, respectively. The rate of OTC adsorption also increased in the samples after annealing. For the Ni0.5Co0.5La0.02Fe1.98O4 sample, the rate improved by 1.8 times. In the case of the Ni0.5Co0.5Gd0.025Fe1.975O4 sample, the rate increased by 3.6 times. The analyzed data shows that the dye and antibiotic molecules are adsorbed on the ferrite's surface through a chemisorption.